2003
DOI: 10.1097/01.tp.0000090395.98045.09
|View full text |Cite
|
Sign up to set email alerts
|

Increasing the donor pool using en bloc pediatric kidneys for transplant

Abstract: Overall graft survival was similar in both groups, vascular complications were the main cause of graft loss in EBPKT, and the EBPKT showed excellent long-term graft function and a low incidence of acute rejection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
39
0
2

Year Published

2006
2006
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 60 publications
(42 citation statements)
references
References 29 publications
1
39
0
2
Order By: Relevance
“…11 A limited number of relatively small series of pediatric donor kidneys report a significantly better long-term outcome for en bloc transplanted pediatric kidneys once they survive the early postoperative course with 5-year survival rates of 76% to 82%. 14,15 Despite encouraging results, there are a few studies that have evaluated the outcomes of kidneys from young pediatric donors. While the results of the en bloc transplants using kidneys from donors between 2 and 5 years of age were similar to solitary transplants from standard criteria donors, worse outcomes have been reported when using similar techniques with kidneys from donors younger than 2 years of age.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…11 A limited number of relatively small series of pediatric donor kidneys report a significantly better long-term outcome for en bloc transplanted pediatric kidneys once they survive the early postoperative course with 5-year survival rates of 76% to 82%. 14,15 Despite encouraging results, there are a few studies that have evaluated the outcomes of kidneys from young pediatric donors. While the results of the en bloc transplants using kidneys from donors between 2 and 5 years of age were similar to solitary transplants from standard criteria donors, worse outcomes have been reported when using similar techniques with kidneys from donors younger than 2 years of age.…”
Section: Discussionmentioning
confidence: 99%
“…While the results of the en bloc transplants using kidneys from donors between 2 and 5 years of age were similar to solitary transplants from standard criteria donors, worse outcomes have been reported when using similar techniques with kidneys from donors younger than 2 years of age. 15 In the United Kingdom, kidneys from pediatric donors up to 5 years old, or up to 15 kg in weight, are offered en bloc for transplant, usually to an adult recipient. In most instances, allocation of these kidneys to recipient is left to the center's discretion.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown comparable long-term graft survival between en bloc kidneys and adult cadaver donor kidneys (16 -18). Serial annual creatinine clearances were significantly better in en bloc kidneys compared to adult cadaver kidneys in the five-year follow-up in one study (18).…”
mentioning
confidence: 96%
“…Several strategies have been employed to reduce this ever-widening gap, which include living donor kidney transplantation, utilizing extended criteria donor kidneys, en-bloc kidneys from pediatric donors and hepatitis-positive donors (1)(2)(3). More recently, kidneys from donation after cardiac death (DCD) donors have been gaining acceptance.…”
Section: Introductionmentioning
confidence: 99%